Application of Linear Programming in Profit Maximization (A Case Study of Crunches Fried Chicken at Miami Tours and Travel Hotel in Kabale District) - Tayebwa, Osbert (Kabale University, 2022)
A Research Report Submitted to the Faculty of Education in Partial Fulfillment of the Requirements for the A Ward of A Bachelors Degree with Education of Kabale University